Endoscopic submucosal dissection with sentinel node navigation surgery for early gastric cancer - Bok, G. H.; Kim, Y. J.; Jin, S. Y.; Chun, C. G.; Lee, T. H.; Kim, H. G.; Jeon, S. R.; Cho, J. Y. (Endoscopy, 2012)
We combined endoscopic submucosal dissection (ESD) and sentinel node navigation surgery with the purpose of achieving complete resection of early gastric cancer while preserving the organ and assessing pathological nodal status. A total of 13 patients with cT1( ≤ 3 cm)N0 early gastric cancer underwent combined ESD and sentinel node navigation surgery (ESN) at a single tertiary referral center. Sentinel node navigation surgery using indocyanine green was performed during ESD and all suspected sentinel nodes were removed laparoscopically and examined intraoperatively. ESN was converted to gastrectomy with D2 dissection if there was evidence of metastasis on frozen section. ESN was completed in 12 patients and in 1 patient was converted to gastrectomy after sentinel node navigation surgery. En bloc tumor resection was achieved in all cases. Two patients underwent additional gastrectomy because they had tumor-positive vertical margins. In all cases ESN was conducted without intraoperative or postoperative adverse events. ESN is a feasible minimally invasive procedure that allows en bloc tumor resection to be achieved while assessing the pathological status of the lymph nodes.